Analisis Keanekaragaman Dekapoda Pada Karang Mati (Genus : Acropora sp.) Di Pantai Pelabuh Dalam Tuing Dan Pantai Turun Aban, Kabupaten Bangka - Umam Kamarullah; Wahyu Adi; Indra Ambalika Syari (Akuatik: Jurnal Sumberdaya Perairan, 2019)
Decapoda is a ten-legged invertebrate organism macro such as shrimp, crabs and lobster. Dekapoda is an association biota with a coral reef ecosystem that has ecological functions, namely as detritus feeders and as a food source for other biota in the food chain in coral reef ecosystems. This aims of this study to analyze the diversity and density of decapods species on dead corals of Acropora sp. at Pelabuh Dalam Tuing and Turun Aban Beach. This research was conducted in July-August 2018 at the Pelabuh Dalam Tuing and Turun Aban Beach. Decapoda data retrieval uses the Dead Coral Head method. The results of the study on Pelabuh Dalam Tuing Beach found 140 individuals from 9 species of Decapoda on Acropora sp dead corals while Turun Aban Beach were found 242 individuals from 11 species. Diversity index values in both study locations 2,510 and 2,533. The uniformity index value in both study locations 0,884 and 0,871. The dominance index values in the two study locations 0,214 and 0,208. Species density in both study locations had an average value of 0.0121 ind/ and 0.0165 ind/.